Temozolomide resistance in glioblastoma multiforme - Lee, Sang Y. (Genes Dis, 2016)
Temozolomide (TMZ) is an oral alkylating agent used to treat glioblastoma multiforme (GBM) and astrocytomas. However, at least 50% of TMZ treated patients do not respond to TMZ. This is due primarily to the over-expression of O(6)-methylguanine methyltransferase (MGMT) and/or lack of a DNA repair pathway in GBM cells. Multiple GBM cell lines are known to contain TMZ resistant cells and several acquired TMZ resistant GBM cell lines have been developed for use in experiments designed to define the mechanism of TMZ resistance and the testing of potential therapeutics. However, the characteristics of intrinsic and adaptive TMZ resistant GBM cells have not been systemically compared. This article reviews the characteristics and mechanisms of TMZ resistance in natural and adapted TMZ resistant GBM cell lines. It also summarizes potential treatment options for TMZ resistant GBMs.